2009
DOI: 10.2118/112535-pa
|View full text |Cite
|
Sign up to set email alerts
|

Well-Integrity Issues Offshore Norway

Abstract: Summary A number of serious well failures in recent years led to investigations of well-integrity issues. The Petroleum Safety Authority Norway (PSA) performed a pilot well-integrity survey based on supervisory audits and requested input from seven operating companies, 12 preselected offshore facilities, and 406 wells. The wells were a representative selection of production and injection wells with variation in both age and development categories. The pilot project indicates that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Casing leaks can occur through faulty pipe joints, corrosion, or mechanical failure due to thermal stresses or overpressuring (52). Vignes & Aadnøy (63) found that leaks through steel tubing and casing accounted for most failures in offshore Norway. Schwind et al (64) observed that 90% of casing failures were attributable to faulty connections.…”
Section: Mechanisms Of Wellbore-integrity Failurementioning
confidence: 99%
“…Casing leaks can occur through faulty pipe joints, corrosion, or mechanical failure due to thermal stresses or overpressuring (52). Vignes & Aadnøy (63) found that leaks through steel tubing and casing accounted for most failures in offshore Norway. Schwind et al (64) observed that 90% of casing failures were attributable to faulty connections.…”
Section: Mechanisms Of Wellbore-integrity Failurementioning
confidence: 99%
“…Erno and Schmitz [1996], for example, reported that 22% of 435 abandoned wells monitored between 1987 and 1993 in Saskatchewan, Canada, were leaking because of well integrity failure. Elsewhere, the Norwegian Petroleum Safety Authority (PSA) has reported that 15% of 323 production wells, and 33% of 83 injection wells drilled between 1970 and 2006 on the Norwegian Continental Shelf (NCS) had some kind of well integrity problem (related to tubing, annulus safety valves, casing or cement), while 7% of these wells had to be shut-in (closed) due to well integrity issues [Vignes and Aadnøy, 2010]. In a more recent investigation, Davies et al [2014] reported that 6.3% of 8030 wells drilled between 1958 and 2013 in the Marcellus shale of Pennsylvania in the northeast United States showed well integrity and barrier failure and 1.3% of these wells were leaking to surface.…”
Section: Water Resources Researchmentioning
confidence: 99%
“…With the development of deepwater drilling technology, wellbore integrity is increasingly under scrutiny. According to the survey of wellbore integrity conducted by Norwegian Petroleum Safety Authority (PSA) on 106 offshore wells with different development years and production categories, 18% of them had problems with wellbore integrity, and 7% of them were forced to close wells because of wellbore integrity, which caused significant environmental and economic losses. , In the process of deep-well testing and production, the high-temperature (HT) flow produced in the deepwater wells will cause additional pressure in casing annulus. If the axial force generated by excessive temperature change is greater than the bearing capacity of the shear pin at the wellhead, the wellhead will move up and seriously threaten wellbore integrity. In Marlin oilfield in the Gulf of Mexico, excessive annular pressure during oil production resulted in the deformation and fracture of the casing and tubing of well A-2 few hours after production .…”
Section: Introductionmentioning
confidence: 99%